2016
DOI: 10.1051/0004-6361/201527943
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur molecules in the circumstellar envelopes of M-type AGB stars

Abstract: Aims. The sulphur compounds SO and SO 2 have not been widely studied in the circumstellar envelopes of asymptotic giant branch (AGB) stars. By presenting and modelling a large number of SO and SO 2 lines in the low mass-loss rate M-type AGB star R Dor, and modelling the available lines of those molecules in a further four M-type AGB stars, we aim to determine their circumstellar abundances and distributions. Methods. We use a detailed radiative transfer analysis based on the accelerated lambda iteration method… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
120
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(143 citation statements)
references
References 42 publications
20
120
3
Order By: Relevance
“…They find a much lower H 2 S abundance than our radiative transfer results for IK Tau (and indeed, all five of our sources), which are a few orders of magnitude higher. The Li et al (2016) results are also in disagreement with the observational SO results found by Danilovich et al (2016) for IK Tau, which show a lower inner abundance of SO with a peak at ∼ 10 16 cm. The Agúndez et al (2010) study covers a similar region of the CSE -beginning at 10 14 cm, further inwards than Li et al (2016) -but primarily focuses on the effect of clumpiness in the CSE.…”
Section: Comparison With Chemical Modelscontrasting
confidence: 67%
See 2 more Smart Citations
“…They find a much lower H 2 S abundance than our radiative transfer results for IK Tau (and indeed, all five of our sources), which are a few orders of magnitude higher. The Li et al (2016) results are also in disagreement with the observational SO results found by Danilovich et al (2016) for IK Tau, which show a lower inner abundance of SO with a peak at ∼ 10 16 cm. The Agúndez et al (2010) study covers a similar region of the CSE -beginning at 10 14 cm, further inwards than Li et al (2016) -but primarily focuses on the effect of clumpiness in the CSE.…”
Section: Comparison With Chemical Modelscontrasting
confidence: 67%
“…ALI has been previously described in detail by Maercker et al (2008) and Schöier et al (2011) and has been implemented to model molecular emission from a wide variety of molecules in those studies and in Danilovich et al (2014Danilovich et al ( , 2016. Our models assume a smoothly accelerating and spherically symmetric CSE created by mass lost at a constant rate by the central AGB star.…”
Section: Radiative Transfer Modelling Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…The SO (1 × 10 −6 ), SiO (5 × 10 −6 ), and CS (1 × 10 −6 ; after correcting the 13 CS abundance by the estimated 12 C/ 13 C ≈ 10) abundances all lie in the range reported for AGB CSEs (Danilovich et al 2016;Schöier et al 2013;Velilla Prieto et al 2017), while the H 2 CO abundance (2 × 10 −6 ; assuming an orthoto-para ratio of 3) is about an order of magnitude higher than in IK Tau (Velilla Prieto et al 2017). CH 3 OH has an estimated abundance of 3 × 10 −6 (assuming an E-to-A ratio of 1), almost two orders of magnitude higher than towards the supergiant IRC+10420 (Quintana-Lacaci et al 2016).…”
Section: Chemistrymentioning
confidence: 63%
“…We note that the abundance of sulphur oxides is yet another mystery in circumstellar chemistry of O-rich stars (e.g. Yamamura et al 1999;Fu et al 2012;Adande et al 2013;Danilovich et al 2016;Velilla Prieto et al 2017). Our results may be indicative of some violent processes, such as shocks, in the formation of NH 3 .…”
Section: Ammonia Chemistrymentioning
confidence: 61%